2007
DOI: 10.1007/s11199-007-9246-9
|View full text |Cite
|
Sign up to set email alerts
|

Israeli Teachers’ Perceptions of Lateness: A Gender Comparison

Abstract: The study examines the relationship between distributive justice and teachers' lateness, focusing on the mediation effect of organizational commitment and taking into account gender differences. The sample consisted of 1,016 teachers from 35 high schools in Israel. Results, based on multi-level analysis, showed that, for women, organizational commitment partially mediated the relation between perceived distributive justice and lateness. No such effect was found for men. The findings are explained in terms of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…However, previous studies have indicated that organizational commitment affects ethical perceptions and withdrawal behaviors such as lateness and absence among other professions (e.g., Shapira-Lishchinsky, 2007;Shapira-Lishchinsky and Rosenblatt, 2010;Podsakoff et al, 2007). This, then, provides the basis for using the Kenny et al (1998) method of measurement, in addition to simple correlations, in order to examine the mediating effect of organizational commitment upon the relationship between ethical perceptions and other withdrawal behaviors such as lateness and absence (in addition to intent to leave).…”
Section: Resultsmentioning
confidence: 99%
“…However, previous studies have indicated that organizational commitment affects ethical perceptions and withdrawal behaviors such as lateness and absence among other professions (e.g., Shapira-Lishchinsky, 2007;Shapira-Lishchinsky and Rosenblatt, 2010;Podsakoff et al, 2007). This, then, provides the basis for using the Kenny et al (1998) method of measurement, in addition to simple correlations, in order to examine the mediating effect of organizational commitment upon the relationship between ethical perceptions and other withdrawal behaviors such as lateness and absence (in addition to intent to leave).…”
Section: Resultsmentioning
confidence: 99%
“…Future studies should explore whether accountability is related to other withdrawal behaviors, such as work lateness. Because absence and lateness behaviors are both associated with organizational ethics (Rosenblatt et al, 2010;Shapira-Lishchinsky, 2007), and because accountability is linked to work ethics (Study 2 above), accountability may well predict a spectrum of withdrawal behaviors other than absence.…”
Section: Personal Accountability In Educationmentioning
confidence: 99%
“…Avoidable lateness (stable periodic lateness) occurs when student's thinks they have better or more important activities to do than arrive on time for a particular lesson or class and in most cases this happens with mathematics classes. Finally, unavoidable lateness is due to factors beyond the student's control, such as transport problems, bad weather, illness and accident (Shapira-Lishchinsky, 2007).…”
Section: Conceptualizationmentioning
confidence: 99%